An Anthropolinguistic Analysis of Language Use in Anti-Female Genital Mutilation Campaign on @puan_amalhayati Instagram Account - A'yunin, Qurrota; Sajarwa, Sajarwa; Firmonasari, Aprillia (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2025)
The Practice of Pemotongan dan/atau Pelukaan Genitalia Perempuan (P2GP) or Female Genital Mutilation/Cutting (FGM/C) remains a serious problem in Indonesia because it is rooted in traditions, religious views, and cultural constructs that have been passed down through generations. The urgency of addressing this topic lies in the medical and social impacts that harm women, as well as the debate over terminology that influences public perception of the practice. This research data was obtained from the Instagram account @puan_amalhayati, which consistently campaigns against FGM/C using alternative terms to replace the term